2019
DOI: 10.5530/jyp.2019.11.76
|View full text |Cite
|
Sign up to set email alerts
|

Powder Microscopic, Physicochemical, HPTLC and Antioxidant Studies on Noccik Kudinir Chooranam – A Polyherbal Siddha Formulation

Abstract: Preparation of NKC Vitex negundo and Piper betle were collected from the nearby places. Allium sativum and Piper nigrum were procured from the market. All the plants were authenticated with reference to floras. The fresh leaves of Vitex negundo and Piper betle were shade dried, along with Piper nigrum and Allium sativum (fresh), powdered coarsely (NKC) and stored in an air tight container (Table 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These studies of these formulations confirmed the presence of all the ingredients such as C. angustifolia, Z. officinale, P. nigrum, E. ribes and T. ammi as per Siddha literature ˝Siddha vaithiya thirattu 4 . Previously these powder microscopic techniques were carried out for noccik kudineer choornam 19 .…”
Section: Powder Microscopic Studiesmentioning
confidence: 99%
“…These studies of these formulations confirmed the presence of all the ingredients such as C. angustifolia, Z. officinale, P. nigrum, E. ribes and T. ammi as per Siddha literature ˝Siddha vaithiya thirattu 4 . Previously these powder microscopic techniques were carried out for noccik kudineer choornam 19 .…”
Section: Powder Microscopic Studiesmentioning
confidence: 99%
“…Plants have been the basis of many traditional medicines throughout the world for thousands of years due to their therapeutic efficacy. It is estimated that herbal medicine in developed countries make up to one fourth; while in developing countries it is up to three fourth of all medicines (1). The use of herbal drugs is rapidly increasing worldwide as the herbal drugs were found to be beneficial in treating mild to moderate diseases in all age groups and in averting illnesses thereby promoting health (2).…”
Section: Introductionmentioning
confidence: 99%